2016
DOI: 10.1186/s13054-016-1556-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of driving pressure on mortality in ARDS patients during lung protective mechanical ventilation in two randomized controlled trials

Abstract: BackgroundDriving pressure (ΔPrs) across the respiratory system is suggested as the strongest predictor of hospital mortality in patients with acute respiratory distress syndrome (ARDS). We wonder whether this result is related to the range of tidal volume (VT). Therefore, we investigated ΔPrs in two trials in which strict lung-protective mechanical ventilation was applied in ARDS. Our working hypothesis was that ΔPrs is a risk factor for mortality just like compliance (Crs) or plateau pressure (Pplat,rs) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
142
2
17

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(169 citation statements)
references
References 23 publications
8
142
2
17
Order By: Relevance
“…Therefore, a change in elastance, which may follow an intervention, indicates a change in lung mechanics which transcends the setting of a specific value of driving pressure. When plateau pressure, tidal volume and PEEP are set within the tight ranges of a protective ventilation, driving pressure per se may not offer any additional advantage over the indices of lung mechanics such as elastance, compliance or plateau pressure as recently shown by Guerin et al (38). Indeed, independently from sophisticated statistics, the best association between outcome and driving pressure instead of tidal volume/kg IBW is self-evident considering the relationship between the two variables:…”
Section: Driving Pressurementioning
confidence: 99%
“…Therefore, a change in elastance, which may follow an intervention, indicates a change in lung mechanics which transcends the setting of a specific value of driving pressure. When plateau pressure, tidal volume and PEEP are set within the tight ranges of a protective ventilation, driving pressure per se may not offer any additional advantage over the indices of lung mechanics such as elastance, compliance or plateau pressure as recently shown by Guerin et al (38). Indeed, independently from sophisticated statistics, the best association between outcome and driving pressure instead of tidal volume/kg IBW is self-evident considering the relationship between the two variables:…”
Section: Driving Pressurementioning
confidence: 99%
“…The role of driving pressure, the current stronger predictor of mortality in ARDS (41), is under investigation. We recently observed that driving pressure share the same information as plateau pressure to predict survival in ARDS patients receiving lung protective mechanical ventilation (42).…”
Section: Evidencementioning
confidence: 96%
“…Pada kelompok risiko dengan delta pressure tinggi, risiko mortalitas akan meningkat 45% bila dibandingkan dengan kelompok subyek dengan delta pressure rendah. 7 Pada penelitian ini digunakan uji statistik chi square, hanya variabel delta pressure yang digunakan sebagai variabel independen dan mortalitas sebagai variabel dependen.…”
Section: Pembahasanunclassified
“…Namun demikian, faktor delta pressure tidak dapat terlepas dari faktor lain yang berpengaruh terhadap luasnya bagian paru yang dapat berfungsi untuk pertukaran oksigen, seperti PEEP dan volume tidal. [18][19][20] Pada penelitan yang dilakukan oleh Guerin dkk 7 disebutkan bahwa faktor delta pressure bukanlah satu-satunya faktor independen dalam memprediksi mortalitas. Faktor besarnya PEEP dan volume tidal yang diberikan juga berkontribusi untuk terjadinya mortalitas.…”
Section: Pembahasanunclassified